2022
DOI: 10.1039/d1cp04725f
|View full text |Cite
|
Sign up to set email alerts
|

Helium structures around SF5+ and SF6+: novel intermolecular potential and mass spectrometry experiments

Abstract: Helium clusters attaching the recently experimentally observed sulphur hexafluoride SF6+ and sulphur pentafluoride SF5+ ions are investigated in a combined experimental and theoretical effort. Mass spectrometry ion yields are obtained...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…In contrast to previous studies where ionization of doped neutral HNDs was typically leading to monotonically decreasing ion abundances of He tagged ions as a function of N , , the maximum of the size distribution of He N Ca 2+ can be shifted to a desired value by setting the evaporation pressure P evap to an appropiate value. Similar profiles in the corresponding ion abundances have been reported in recent studies of the He N SF 5 + and He N SF 6 + clusters . Peaks at N = 12, 32, 44, and 74 separate specific ranges of sizes (denoted as A, B, and C in Figure ).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…In contrast to previous studies where ionization of doped neutral HNDs was typically leading to monotonically decreasing ion abundances of He tagged ions as a function of N , , the maximum of the size distribution of He N Ca 2+ can be shifted to a desired value by setting the evaporation pressure P evap to an appropiate value. Similar profiles in the corresponding ion abundances have been reported in recent studies of the He N SF 5 + and He N SF 6 + clusters . Peaks at N = 12, 32, 44, and 74 separate specific ranges of sizes (denoted as A, B, and C in Figure ).…”
supporting
confidence: 80%
“…In this process weakly bound He atoms are first removed, which leads to intensity anomalies at numbers of He atoms N attached that have different evaporation energies compared to neighboring numbers. Shell closures will lead to pronounced intensity drops for larger sizes and magic numbers to exceptionally intense peaks at a given N. The appearance of especially stable structures is thereby not dependent on the evaporation pressure, 33 however, when its value increases the maximum yield of He solvated ions shifts to lower He numbers which is essential for the identification of intensity anomalies at small values of N. Martini et al recently demonstrated that He tagged dopant ions can also be formed efficiently upon surface collisions of charged and doped He droplets; 34 however, this method does not allow the tuning of the average number of He atoms attached.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15% of the measured ion yield at mass 178 u (the mass of the parent Ph anion) arises from the dehydrogenated anion (Ph-H) À that contains one 13 C and 15% of the measured ion yield at mass 179 u arises from the bare Ph anion, contributing to the protonated Ph peak. In contrast to the stabilization of the transient molecule SF 6 + in HNDs by the formation of SF 5 + F clusters, 41,42 in the present case, the ultracold HND environment enables the stabilization of bare as well as dehydrogenated Ph anions.…”
Section: Anions Extracted From Doped Hndsmentioning
confidence: 71%
“…The Lennard-Jones parameters of a pair of interacting molecules consist of two components related to intermolecular interactions: the collision diameter, the separation distance at which the intermolecular potential energy equals zero, and the well depth, the minimal value of the intermolecular potential energy. In the literature, optimizing initially guessed potential parameters by using macroscopic thermophysical property data as optimization constraints 4,5 or by using transport data combined with the inversion of the Chapman-Enskog relations 25,32,33 as well as experimental measurements using neutron/X-ray diffraction, 34,35 molecular beam scattering, 26,36 or spectroscopy [37][38][39] were the primary means to obtain Lennard-Jones parameters. Lennard-Jones parameters optimized from macroscopic data are a posteriori estimates and often involve the empirical Lorentz-Berthelot or modified Lorentz-Berthelot combining rule to describe cross interactions.…”
Section: Introductionmentioning
confidence: 99%